2011
DOI: 10.1073/pnas.1100987108
|View full text |Cite
|
Sign up to set email alerts
|

F-box protein MAX2 has dual roles in karrikin and strigolactone signaling in Arabidopsis thaliana

Abstract: Smoke is an important abiotic cue for plant regeneration in postfire landscapes. Karrikins are a class of compounds discovered in smoke that promote seed germination and influence early development of many plants by an unknown mechanism. A genetic screen for karrikin-insensitive mutants in Arabidopsis thaliana revealed that karrikin signaling requires the F-box protein MAX2, which also mediates responses to the structurally-related strigolactone family of phytohormones. Karrikins and the synthetic strigolacton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
409
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 404 publications
(438 citation statements)
references
References 56 publications
14
409
0
3
Order By: Relevance
“…In addition, strigolactones and analogous chemicals (i.e., karrikins) regulate seed germination as part of a light-dependent process (Tsuchiya et al 2010;Nelson et al 2011). Because of their role in plant growth and development, strigolactones are considered an additional class of hormones besides the already well-established hormone groups.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, strigolactones and analogous chemicals (i.e., karrikins) regulate seed germination as part of a light-dependent process (Tsuchiya et al 2010;Nelson et al 2011). Because of their role in plant growth and development, strigolactones are considered an additional class of hormones besides the already well-established hormone groups.…”
Section: Introductionmentioning
confidence: 99%
“…Perception of and signaling by karrikins, compounds originally identified in the smoke of forest fires, are also associated with D3 and KAI2, an α/β hydrolase that is highly homologous to D14 [18]. Recent studies have identified the putative transcriptional repressor D53 [19,20] as well as the transcription factor BES1 as SCF D3 substrate targets in response to SL exposure and the D53 paralog SMAX1 in response to karrikin exposure.…”
Section: Introductionmentioning
confidence: 99%
“…The d3/max2/rms4 mutants are also SL insensitive 1,2 . D3/ MAX2/RMS4 genes encode members of the F-box-family protein [17][18][19][20] that participate in an Skp-cullin-F box (SCF) complex 18 and have diverse roles in the plant lifecycle 14,[21][22][23][24][25][26][27][28][29][30] . Recently, it has been reported that petunia DAD2, an orthologue of rice DWARF14 (D14) protein, can hydrolyse the enol ether linkage of GR24 and interacts with PhMAX2A, a petunia orthologue of Arabidopsis MAX2 protein, indicating that the formation of the DAD2-PhMAX2A complex initiates an SCF-mediated signal transduction pathway 31 .…”
mentioning
confidence: 99%